EFFICIENCY OF GROWING MAJOR CROPS ON SOILS RELEASED FROM HORTICULTURE UNDER THEIR OPTIMIZED FERTILIZATION - Melnyk В.; Riazanov С.; Pryimak Ю. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
One of the main methods to improve the economic efficiency of grain production apart from the garden uprooting is to provide plants with the main nutrients: nitrogen, phosphorus, and potassium through the rational and science-based mineral fertilization of soils, taking into account the presence of nutrients in them. The article deals with the transfer of soils after perennial plantations into the use for field crop rotation on gray forest soils for growing the major crops with optimized fertilization on the example of the farm in Vinnytsia region in the conditions of the Forest-Steppe of Right-Bank Ukraine. The economic efficiency of the elements of the crop cultivation technology was calculated based on the weighted average selling prices for the grown products and prices for mineral fertilizers in 2021. Two variants of the rate of application of mineral fertilizers under the planned yield of winter wheat at the level of 7.0 t/ha, corn 11.2 t/ha, and sunflower 3.5 t/ha considered the available nutrients in the soil. It was established that in the variant after intensive horticulture, the soil needed more fertilizers. Thus, for growing winter wheat, there was an increase in production costs for grown products by UAH 1,636/ha, for corn by UAH 2,041.5/ha, and for sunflower by UAH 2,132/ha, respectively, compared to the option after an extensive garden. It was established that in the variant of cultivation after extensive horticulture under winter wheat, corn, and sunflower, the yield increase is noted by 0.397, 0.497 and 0.107 t/ha respectively. It was found that after extensive horticulture, the level of profitability was higher by 27.9 % for the cultivation of winter wheat, by 29.4 % – for corn, and by 31.5 % – for sunflower.